Pedagogical Conditions of Readiness of Future Economists to Professional Communication - Yaroshchuk, Iryna (Pedagogical Discourse, 2013)
The article explores the definitions of the problem of training of the future economists for professional communication. The essence of «professional communication of economist» is grounded. The essence and structure of communicative readiness of future economist which consists of motivational, contextual and operational and procedural components are considered. The complex of pedagogical conditions forming the future economist readiness for professional communication is determined.